Language task design: Teachers’ understanding and practices in teaching writing - Laxman Prasad Bhandari (English Language Teaching and Research Journal (ELTAR-J), 2020)
This study was designed to explore English language teachers’ understanding of task-based language teaching and their practices of designing tasks for teaching writing. In the first part, I discuss the concept of task-based language teaching, tasks, and task design connecting with my experiences within the framework of the socio-cultural approach to second language acquisition. I used both unstructured and semi-structured interview questions to explore the lived experiences of secondary level English teachers of community schools of Nawalparasi district in Nepal. The study reveals mixed responses of participants in understanding task-based teaching and language tasks though they held positive perceptions toward the phenomenon. The findings suggest that teachers design tasks incorporating textual exercises as well as their (both students and teachers) experiential life events for teaching writing according to their students’ level, need, and interest for teaching writing. The study further reveals that teachers design both different tasks to address the diverse learning abilities of the students. However, the findings also show that more exposure is needed to enable teachers to design more suitable tasks for teaching writing.